Immune responses in diabetic nephropathy: Pathogenic mechanisms and therapeutic target - Chen, Jiahao; Liu, Qinhui; He, Jinhan; Li, Yanping (Frontiers in immunology, 2022)
Diabetic nephropathy (DN) is a chronic, inflammatory disease affecting millions of diabetic patients worldwide. DN is associated with proteinuria and progressive slowing of glomerular filtration, which often leads to end-stage kidney diseases. Due to the complexity of this metabolic disorder and lack of clarity about its pathogenesis, it is often more difficult to diagnose and treat than other kidney diseases. Recent studies have highlighted that the immune system can inadvertently contribute to DN pathogenesis. Cells involved in innate and adaptive immune responses can target the kidney due to increased expression of immune-related localization factors. Immune cells then activate a pro-inflammatory response involving the release of autocrine and paracrine factors, which further amplify inflammation and damage the kidney. Consequently, strategies to treat DN by targeting the immune responses are currently under study. In light of the steady rise in DN incidence, this timely review summarizes the latest findings about the role of the immune system in the pathogenesis of DN and discusses promising preclinical and clinical therapies.